Effect of Urtica dioica L. on Selected Trace Elements Levels and Serum Protein Patterns in the Rabbits Treated with 7,12-dimethylbenz(a)anthracene - Ekin, Suat; Oto, Gokhan; Berber, Ismet; Turel, Idris; Kusman, Tuba (Asian Journal of Chemistry, 2010)
In the present study, the effect of Nettle (Urtica dioca L.) on trace elements and serum protein patterns in female rabbits administrated to 7,12-Dimethylbenz(a)anthracene (DMBA) was investigated. Rabbits were divided into equal four groups. Group I was control group (n = 8), group II (n = 8), treated with DMBA (1 mg/kg.d), group III treated with DMBA (1 mg/kg.d) and methanol extract of U. dioica 35 mg/kg/d and group IV (n = 8) treated with DMBA (1 mg/kg.d) and aqueous extract of U. dioica 35 mg/kg/d. The results show that on 60th day DMBA-treated group were compared with the control group levels, a significant decrease (p < 0.05) was observed in the Zn. DMBA and methanol extract of U. dioica treated group were compared with the control group levels, a significant increase (p < 0.05) was observed in the Cu. Serum Fe and Mn levels among groups were determined not to be statistically significant (p > 0.05). It was found that U. dioica not affected on trace elements level and serum protein patterns in rabbits subjected to DMBA.